Prognostic significance of myocardial salvage assessed by cardiac magnetic resonance in reperfused ST-segment elevation myocardial infarction - Li, Yunling; Wang, Guokun; Wang, Xueying; Li, Ye; Zhao, Yanming; Gu, Xia; Xu, Bing; Cui, Jinjin; Wang, Xuedong; Sun, Yong; Liu, Shengliang; Yu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Aims Myocardial salvage index (MSI) is attracting increasing attention for predicting prognosis in acute myocardial infarction (AMI); however, the evaluation of MSI is mainly based on contrast agent-dependent cardiac magnetic resonance (CMR) scanning sequences. This study aims to investigate the prognostic value of MSI in reperfused ST-segment elevation myocardial infarction (STEMI) through the contrast agent-free CMR technique. Methods and results Nighty-two patients with acute STEMI, who underwent CMR after primary percutaneous coronary intervention (PPCI), were finally enrolled. Patients were subcategorized into two groups according to median MSI. T1 and T2 mapping were conducted for measuring infarct size (IS) and area at risk (AAR). IS was significantly larger in < median MSI group than ≥ median MSI group (P < 0.001). AAR between the two groups showed no obvious differences (P = 0.108). Left ventricular ejection fraction (LVEF) was lower in < median MSI group than ≥ median MSI group (P = 0.014). There was an obvious inverse correlation between MSI and reperfusion time (R = –0.440, P < 0.001) and a strong inverse correlation between MSI and IS (R = –0.716, P = 0.011). As for the relationship LVEF, MSI showed positive but weak correlation (R = 0.2265, P < 0.001). Over a median follow-up period of 263 (227–238) days, prevalence of MACEs was significantly higher in the < median MSI group [HR: 0.15 (0.04–0.62); Log-rank P = 0.008]. The univariate Cox regression analysis revealed that LVEF, IS, and MSI were significant predictors for major adverse cardiovascular events (MACEs) (all P < 0.05). In the stepwise multivariate Cox regression analysis, LVEF and MSI were identified as independent parameters for predicting MACEs (both P < 0.05). In the receiver-operating characteristic analysis, LVEF, IS, and MSI showed prognostic value in predicting MACEs with AUCs of 0.809, 0.779, and 0.896, respectively, all (P < 0.05). A combination of MSI with LVEF showed the strongest prognostic value of MACEs (AUC: 0.901, sensitivity: 77.78%, specificity: 98.80%, P < 0.001). Delong’s test showed that the combination of LVEF with MSI had an incremental value than LVEF itself in predicting MACEs (P = 0.026). Conclusion Contrast agent-free CMR technique provides a reliable evaluation of MSI, which contributes to assessing the efficacy of reperfusion therapy and predicting the occurrence of MACEs.